Oral Pathogen Fusobacterium nucleatum Coaggregates With Pseudomonas aeruginosa to Modulate the Inflammatory Cytotoxicity of Pulmonary Epithelial Cells - Li, Qian; Wang, Hongyan; Tan, Lisi; Zhang, Shuwei; Lin, Li; Tang, Xiaolin; Pan, Yaping (Frontiers in Cellular and Infection Microbiology, 2021)
Chronic obstructive pulmonary disease (COPD) is the third leading cause of mortality worldwide, and inflammatory damage induced by bacterial infections is an important contributor to the etiology of COPD. Fusobacterium nucleatum, a recognized periodontal pathogen, is considered as a biomarker of lung function deterioration of COPD patients coinfected with Pseudomonas aerugionsa, but the underlying mechanism is still unclear. This study established single- and dual-species infection models, bacterial simultaneous and sequential infection models, and found that F. nucleatum could coaggregate with P. aeruginosa to synergistically invade into pulmonary epithelial cells and transiently resist P. aeruginosa-induced cytotoxic damage to amplify IL-6 and TNF-α associated inflammation in pulmonary epithelial cells simultaneously infected with P. aeruginosa and F. nucleatum. Furthermore, F. nucleatum pretreatment or subsequential infection could maintain or even aggravate P. aeruginosa-induced inflammatory cytotoxicity of pulmonary epithelial cells. These results indicate that oral pathogen F. nucleatum coaggregates with P. aeruginosa to facilitate bacterial invasion and modulates the inflammatory cytotoxicity of pulmonary epithelial cells, which may contribute to lung function deterioration of COPD patients accompanied with P. aeruginosa and F. nucleatum coinfection.